2021
DOI: 10.18295/squmj.4.2021.009
|View full text |Cite
|
Sign up to set email alerts
|

Virtual Microscopy in Undergraduate Pathology Education

Abstract: Objectives: Whole-slide imaging (WSI) and virtual microscopy (VM) have revolutionized teaching, diagnosis and research in histopathology. The aims of this study were to establish the feasibility of achieving early integration of clinical reasoning with undergraduate pathology teaching on a virtual microscopy platform and, to determine its student-centricity through student feedback. Methods: Thirty-eight VM-centered clinical cases were introduced to forty-nine students in an integrated undergraduate medical cu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 24 publications
1
5
0
Order By: Relevance
“…Various types of learning technologies were represented including technologies created specifically to support learning such as bespoke elearning modules, [21][22][23][24] virtual patients, 25-28 assessments [29][30][31][32][33][34][35][36][37][38][39][40] and mobile apps for learning. [41][42][43][44][45][46][47][48][49] Other technologies have been repurposed as learning technologies such as social media, 50,51 medical technologies-including digital microscopy, phonocardiography and digital X-rays, [52][53][54][55][56][57][58][59][60][61] and virtual and augmented reality. [62][63][64][65][66][67][68][69][70][71] Regardless of the nature of the technology, about a third of the identified articles ...…”
Section: Samr Categorisationmentioning
confidence: 99%
See 1 more Smart Citation
“…Various types of learning technologies were represented including technologies created specifically to support learning such as bespoke elearning modules, [21][22][23][24] virtual patients, 25-28 assessments [29][30][31][32][33][34][35][36][37][38][39][40] and mobile apps for learning. [41][42][43][44][45][46][47][48][49] Other technologies have been repurposed as learning technologies such as social media, 50,51 medical technologies-including digital microscopy, phonocardiography and digital X-rays, [52][53][54][55][56][57][58][59][60][61] and virtual and augmented reality. [62][63][64][65][66][67][68][69][70][71] Regardless of the nature of the technology, about a third of the identified articles ...…”
Section: Samr Categorisationmentioning
confidence: 99%
“…Various types of learning technologies were represented including technologies created specifically to support learning such as bespoke elearning modules, 21–24 virtual patients, 25–28 assessments 29–40 and mobile apps for learning 41–49 . Other technologies have been repurposed as learning technologies such as social media, 50,51 medical technologies—including digital microscopy, phonocardiography and digital X‐rays, 52–61 and virtual and augmented reality 62–71 . Regardless of the nature of the technology, about a third of the identified articles described technology use at the level of substitution and almost a half at augmentation (Table 2).…”
Section: Technology‐led Transformations In Hpe: Literature Exploratio...mentioning
confidence: 99%
“…Results from various studies revealed significantly improved academic test scores [20,31,32,[36][37][38]46,48,50,52,53,58,62,63] along with improvements in the medical knowledge of students [22,34,38,[44][45][46]48,55,58,61,63,64,67].…”
Section: Vm Podcastmentioning
confidence: 99%
“…Development of diagnostic and practical skills during laboratory sessions was an important finding [33,39,48,53,56,58,59,64]. Studies also reported that VM promotes selfdirected learning [31,35,38,41,48,58,59,64] and thus an overall better method of learning for exam preparation for the students [32,38,52,53,56].…”
Section: Vm Podcastmentioning
confidence: 99%
See 1 more Smart Citation